Advancing chronic pain care in Canada: History and impact of the Canadian Pain Task Force - Fiona Campbell; Manon Choinière; Hani El-Gabalawy; Jacques Laliberté; Michael Sangster; Jaris Swidrovich; Linda Wilhelm; Maria Hudspith (Canadian Journal of Pain)
In 2019, Health Canada established the Canadian Pain Task Force. Through this commitment, Canada joined other countries, such as the United States and Australia, in creating a national-level mechanism to support work in the area of chronic pain. This article provides a historical narrative of national and regional advocacy and efforts that led to creation of the Task Force, the broad representation of its members, as well as its mandate and goals. Subsequently it outlines the Task Force’s progression through three distinct phases, each marked by extensive consultation and culminating in a comprehensive report submitted to Health Canada. A particular focus is placed on the third phase, which resulted in the formulation of An Action Plan for Pain in Canada, and we present an overview of the recommendations contained therein. Moreover, the article situates the Canadian Pain Task Force within the broader movement to transform how pain is recognized, understood, and treated in Canada. It highlights initial steps taken to address identified priorities, indicating a proactive approach toward effecting meaningful change.